Ischaemic stroke subtypes and associated risk factors: a French population based study. Issue 12 (27th June 2008) - Bejot, Y; Caillier, M; Ben Salem, D; Couvreur, G; Rouaud, O; Osseby, G-V; Durier, J; Marie, C; Moreau, T; Giroud, M
Abstract : Background: There is little reliable population based information about the distribution of risk factors among the various ischaemic stroke subtypes, even though determining risk factor profiles is of major importance to develop targeted preventive strategies. Methods: The distribution of first ever ischaemic stroke subtypes was established in a prospective population based study conducted in Dijon, France (152 606 inhabitants). Cases were collected between January 2005 and December 2006, and were classified using TOAST classification. Vascular risk factors were recorded to determine a risk factor profile for each subtype. Results: 332 patients with first ever ischaemic stroke (150 men and 182 women) were recorded. Adjusted incidence to world population was 54/100 000/year. The distribution of ischaemic stroke subtypes was as follows: 119 (35.8%) cases of large artery atherosclerosis, 89 (26.8%) small artery occlusions, 81 (24.4%) cardioembolisms and 43 (13%) other and undetermined causes. The most frequent vascular risk factor was hypertension, irrespective of the ischaemic stroke subtype, with a total prevalence of 62%. Using multivariate regression, a positive association between cardioembolism and age (OR 1.051; 95% CI 1.026 to 1.076; p<0.001) was demonstrated and between small artery occlusion and either high blood pressure (OR 1.86; 95% CI 1.06 to 3.27; p = 0.03) or hypercholesterolaemia (OR 2.23; 95% CI 1.33 to 3.76; p = 0.02). Conclusion: This comprehensive prospective population based study has demonstrated that vascular risk factors exhibit a particular distribution according to the ischaemic stroke subtypes. These findings, as well as the great frequency of hypertension among stroke patients, have implications for prevention strategies, the design of clinical trials and the organisation of health care services.